论 “民众联络所” 的翻译功能及社会属性 = A study on the translation function and social qualities of “Community Centre” - 项慧菲 Xiang, Huifei (2019)
“民众联络所”作为新加坡华语特有词汇，反映了新加坡独特的社会结构形态，在新加坡政治与社会发展过程中扮演着重要角色。本文将“民众联络所”这一译词放置于社会宏观语境下考察，研究“民众联络所”在新加坡不同历史时期如何受到政治与社会因素的操纵和制约。从目的论的角度探讨译词随着社会发展如何被赋予特定的社会属性和意识形态，并发挥一定的翻译功能，传达所需要的社会意识和社会价值观。本文认为，在新加坡社会语境下译词不仅仅充当信息的载体和传播的中介，还有改变社会形态、巩固政权、发展新思想的功能，对国家建设和社会发展都起着巨大的推动作用。 “Min Zhong Lian Luo Suo” is a unique representative of Chinese Vocabulary within Singapore’s social context. It represents Singapore’s unique social formation and plays an important role in the political and societal development of Singapore. This paper aims to examine “Min Zhong Lian Luo Suo” via social macro context to study how “Min Zhong Lian Luo Suo” was maniplated and restricted by political and social factors during different historical periods. Using Skopos theory, this paper will also analyze on how the term “Min Zhong Lian Luo Suo” is a form of rewriting produced by Singapore’s ideological and political constraints within its social context, hence displaying certain translation function to relay social awareness and values. And this paper argues that the term “Min Zhong Lian Luo Suo” not only act as the carrier of information and communication media, it also has the function to change the social formation and stabilize politics as well as developing new thoughts, which was an important driving force for the development of the country and society.